Wie kam Georg Simmel zur Modernen? - Rammstedt, Otthein (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2020)
The article offers a detailed and in-depth insight into the use and meaning of the concept “modern” by Georg Simmel. From the late 1880s onwards, Simmel presents himself as part of the Naturalism movement – which he also calls “movement of the new culture” – and he continued using the word “modern”. In reviewing his oeuvre, it is noticeable that ‘modern’ was first used by him in the late 1880s, and then excessively so in the early 1890s, with a view to a concrete object, namely the “modern worldview”, or “modern philosophy of life”; from the mid-1890s ‘modern’ ceased in his works, and he now focused on “modern culture” in the broader sense and on “modern lifestyle” in “The Philosophy of Money” (1900). The positive connotation of the term ‘modern’ is almost completely lost in Simmel’s publications as well as in his private letters during the war years 1914 to 1918, and if so, the time frame of ‘modern’ extends over decades, even centuries, probably with the function of making the shortcomings of the present comprehensible. After ascertaining what Simmel meant by ‘modernity’, the author addresses three fundamental aspects of Simmel’s conception of modernity, namely his remarks on lifestyle and his method of investigation that starts directly from the simply given object or ‘thing’ and connects it with the last spiritual meanings. Two closely related characteristics of Simmel’s further work are based on this method: he was the first sociologist who was able to start with things – the handle, the frame, the ruin, the jewellery, the bridge, the door, the chair, etc. – so that he was praised as the inventor of “thing sociology”, and in the 1890s he found the type of text that seemed appropriate for his thinking: the philosophical essay.